PENGAWASAN KOPERASI USAHA EKONOMI DESA SIMPAN PINJAM (UED-SP) - Yeni Anggraini; Wahiruddin Wadin; Suardi Jasma (Jurnal Pendidikan Sepanjang Hayat, 2019)
The general objective of this study was to examine the cooperative supervision of the savings and loan village economic business (UED-SP) Talang Pauh Jaya. The method used in this research is qualitative which objectively describes the supervision of cooperatives of the savings and loan village economic business (UED-SP) Talang Pauh Jaya in Talang Pauh Village, Pondok Kelapa District, Bengkulu Tengah Regency. with data collection techniques namely interviews, observation, and documentation. The research subjects were the Chairperson of  UED-SP Talang Pauh Jaya (Mr. Yanap), Secretary of the UED-SP Talang Pauh Jaya (Mr. Suprayitno) and Treasurer of the UED-SP Talang Pauh Jaya (MrArdiansyah). To prove the magnitude of the data, data was checked using triangulation techniques, time triangulation and subject triangulation. Data is analyzed through stages namely data reduction, data presentation, and conclusion drawing. From the results of the study found results, namely: First, there is the planning of the work of the Talang Pauh Jaya UED-SP, which was previously agreed upon. Second There are irregularities / problems in the UED-SP cooperative Talng Pauh Jaya. Third, there is a form of control over irregularities / problems that occur at UED-SP Talang Pauh Jaya.  Keywords: Job planning, irregularities, problems, forms of controlling irregularities